Interleukin (IL)‐17A, F and AF in inflammation: a study in collagen‐induced arthritis and rheumatoid arthritis. (September 2014) - Sarkar, S.; Justa, S.; Brucks, M.; Endres, J.; Fox, D. A.; Zhou, X.; Alnaimat, F.; Whitaker, B.; Wheeler, J. C.; Jones, B. H.; Bommireddy, S. R.
Summary Interleukin (IL)‐17 plays a critical role in inflammation. Most studies to date have elucidated the inflammatory role of IL‐17A, often referred to as IL‐17. IL‐17F is a member of the IL‐17 family bearing 50% homology to IL‐17A and can also be present as heterodimer IL‐17AF. This study elucidates the distribution and contribution of IL‐17A, F and AF in inflammatory arthritis. Neutralizing antibody to IL‐17A alone or IL‐17F alone or in combination was utilized in the mouse collagen‐induced arthritis (CIA) model to elucidate the contribution of each subtype in mediating inflammation. IL‐17A, F and AF were all increased during inflammatory arthritis. Neutralization of IL‐17A reduced the severity of arthritis, neutralization of IL‐17A+IL‐17F had the same effect as neutralizing IL‐17A, while neutralization of IL‐17F had no effect. Moreover, significantly higher levels of IL‐17A and IL‐17F were detected in peripheral blood mononuclear cells (PBMC) from patients with rheumatoid arthritis (RA) in comparison to patients with osteoarthritis (OA). IL‐17A and AF were detected in synovial fluid mononuclear cells (SFMC) in RA and OA, with IL‐17A being significantly higher in RA patients. Enriched CD3+ T cells from RA PBMCs produced singnificantly high levels of IL‐17A and IL‐17AF in comparison to OA peripheral blood CD3+ T cells. IL‐17A, F and AF were undetectable in T cells from SFMCs from RA and OA. While IL‐17A, F, and AF were all induced during CIA, IL‐17A played a dominant role. Furthermore, production of IL‐17A, and not IL‐17F or IL‐17AF, was elevated in PBMCs, SFMCs and enriched peripheral blood CD3+ T in RA.